Evaluation of palatal rugae pattern in different sagittal skeletal relationships in orthodontic patients - Faezeh Heydari; Hemmat Gholinia; Reza Ghorbanipour (Babol University of Medical Sciences, 2021)
Introduction: Palatal rugae is a collection of mucosal folds in front of the palatal and is unique to each individual. Rugae have been studied for various purposes. This research investigates the pattern of palatal rugae with different skeletal relationships in the sagittal dimension in a group of the Iranian population. Materials & Methods: A cross-sectional study was examined on 135 pre-orthodontic dental casts. The patients were grouped as Class I, Class II, and Class III according to the Nasion -A to Nasion -B angle (ANB) 45 patients in each group. Palatal rugae were recorded based on length, orientation, and pattern in each group, then compared. Data were analyzed by Chi-square, ANOVA, and Tukey post hoc test. In this study p<0.05 was considered significant. Results: The mean number of total rugae was significantly different among groups (p value=0.02). Cl III malocclusion had less number of rugae in comparison to other groups (p value=0.03). The number of straight pattern was significantly different between groups, (p value=0.04) and Cl I malocclusion had  more straight pattern than other groups . Conclusion:This study showed some differences in the palatal rugae pattern between different classes of malocclusion according to Angle's classificatin. In addition, orientation of some rugae were also found to be significantly different between malocclusion  groups.